2016
DOI: 10.1113/jp272320
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of acute and prolonged cAMP agonist exposure on protein kinase A activation and human myometrium contractile activity

Abstract: KEY POINTS SUMMARY Over 15 million babies are born prematurely each year with approximately 1 million of these babies dying as a direct result of preterm delivery. β 2 -adrenoreceptor agonists that act via cAMP can reduce uterine contractions to delay preterm labour, but their ability to repress uterine contractions lasts ≤ 48 hours and their use does not improve neonatal outcomes. Previous research has suggested that cAMP inhibits myometrial contractions via protein kinase A (PKA) activation, but this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 78 publications
(141 reference statements)
0
24
0
Order By: Relevance
“…However, the role of PKA in the cAMP downstream signalling pathway remains unclear in the myometrium. It has been recently reported that the exchange protein directly activated by cAMP (EPAC) rather than PKA may play the major role in cAMP-induced uterine relaxation 24 . Further studies will be required to better understand the mechanism of cAMP-induced uterine relaxations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of PKA in the cAMP downstream signalling pathway remains unclear in the myometrium. It has been recently reported that the exchange protein directly activated by cAMP (EPAC) rather than PKA may play the major role in cAMP-induced uterine relaxation 24 . Further studies will be required to better understand the mechanism of cAMP-induced uterine relaxations.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting, immunodetection and horse radish peroxidase (HRP)-based enhanced chemiluminescence (ECL) imaging were undertaken as previously described (Lai et al , 2016); Novex® Sharp pre-stained protein standards (Life Technologies, Paisley, UK) were used as molecular weight markers. Additionally, Ponceau-stained PVDF membranes were imaged by placing them between sheets of transparency film and scanning them using a Scanjet 4850 desktop scanner (Hewlett Packard, Reading, UK) to save as Tag Image File Format (TIFF) files at 600 dots per inch (dpi) resolution.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Tissue strips were mounted to MLT0201 transducers (ADInstruments, Oxford, UK) attached to an 8channel organ bath (Panlab; Barcelona, Spain), using the polyester threads tied to them during 24 h tissue culture after glass beads had been detached. Organ bath chambers were filled with physiological saline solution (PSS; same composition as previously used (Lai et al, 2016)), which was maintained at 37 o C with 95 % O 2 /5 % CO 2 aeration. Tissues were submerged into these PSSfilled chambers, which contained combinations of 100 nM P4, 1 µM RU-486 and vehicle controls that matched their 24 h treatment conditions, immediately after securing them to their transducers.…”
Section: Isometric Tension Measurements and Data Analysismentioning
confidence: 99%
“…After 25 minutes of oxytocin stimulation, tissues were bathed in PSS containing 60 mM KCl (KPSS) for 10 minutes to confirm viability by maximal depolarisation, after which the KPSS was replaced with PSS and tissues were bathed for a further 10 minutes before the experiment was terminated. All contractility data was analysed using LabChart 6 software (ADInstruments) to calculate mean integral tension values as previously described [22]. Spontaneous contractile output was measured from the 30-minute period immediately before oxytocin/H 2 O addition to tissues.…”
Section: Ex Vivo Isometric Tension Measurements Of Mouse Myometrial Tmentioning
confidence: 99%